Digital Social Enterprises: How Technology Empowers Grassroots Economic Movements - Hiras Pasaribu; Adam Mudinillah; Krim Ulwi (Yayasan Adra Karima Hubbi, 2025)
Background. The growing digitalization of global economies has opened new pathways for economic inclusion, particularly at the grassroots level. Traditional economic development models often fail to reach marginalized communities due to structural barriers, limited resources, and top-down intervention frameworks. In response, digital social enterprises (DSEs) have emerged as transformative agents that leverage technology to drive local entrepreneurship, community resilience, and inclusive innovation. These enterprises utilize digital tools such as mobile applications, blockchain, e-commerce, and social media platforms to empower underserved populations and promote sustainable livelihoods. Purpose. This study aims to examine how technology-enabled social enterprises contribute to the empowerment of grassroots economic movements across diverse socio-economic contexts. Method. The research adopts a qualitative multiple case study design, analyzing six DSEs operating in Southeast Asia, Sub-Saharan Africa, and Latin America. Data were collected through in-depth interviews with founders and beneficiaries, field observations, and analysis of digital engagement metrics. Results. Findings indicate that digital social enterprises significantly enhance economic agency at the grassroots by reducing transaction costs, increasing market access, and facilitating peer-to-peer support networks. Furthermore, technology fosters adaptive capacity and local ownership, enabling communities to co-create solutions tailored to their socio-cultural realities. Conclusion. In conclusion, DSEs represent a viable bottom-up model of economic empowerment where technology serves as both a tool and a catalyst for systemic change. The study offers insights for policymakers, educators, and development practitioners seeking to scale inclusive, tech-driven economic solutions that bridge the digital divide and promote social equity.